Regulasi Diri dan Motivasi Berprestasi: Analisis Korelasi dan Pengamatan kepada Perilaku Kerja Penyuluh Pertanian - Utami Puji Lestari; Samsul Arifin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The success of agricultural extension will run smoothly and produce quality agricultural products to be able to prosper the lives of farmers in Mojokerto Regency, for that we need an extension worker who has good self-regulation to regulate his own behavior so that it can increase motivation to excel in carrying out tasks and efforts. achieve goal attainment. This explanatory research uses accidental sampling technique and involves 50 respondents. Testing tool with SPSS 24. Analysis tool is correlation analysis. A study with the results of a real and positive relationship between self-regulation and achievement motivation of agricultural instructors in Mojokerto Regency